Gestión de marketing digital en la Empresa D'javigym en la ciudad de Babahoyo. - Avegno Urquiza, Nayeli Nahomi (2023)
The present case study carried out within the company D'JAVI GYM to publicize the shortcomings regarding the application of strategies in online marketing raised in the gym, aims to determine the management of digital marketing of the company D' JAVI GYM, so that it gains traction and social recognition in the widest and safest way. Therefore, according to the perception of the frequent clients of the gym, it was observed that it was important to carry out this case study, since it is considered important that companies update themselves because we are in the digital age and any valid promotion for the company is with the use of the same. With the completion of the interview with 136 people, both those who have attended and have not attended the gym, it was observed that clients realize the lack of good management in the digital marketing of the company, they consider it necessary for the company to Create a web page where they can view training plans, online payments, complaint mailboxes or quick messages, quotes, etc. A web page is important for companies to obtain social recognition in an adequate way, with the interview we observed that the company only has 2 social networks, which are Instagram and Facebook and they do not have a person in charge of developing strategies to carry out the their growth, therefore, they need to improve a lot in terms of their management in digital marketing, since they do not have a marketing department with people in charge of what the company must implement for its proper management, it generates shortcomings and loss of opportunities to make the company increase its clients and become more socially recognized, they need to evaluate their own performance and see what they could improve to achieve their objectives.